Fostering Students’ Creativity in English Writing Class: Investigating The Impact of Project-Based Learning in Bridging Ideas and Words - Kurniawati, Farida Nova (Universitas Muhammadiyah Malang, 2023)
The lack of stimulation for students' creativity in English language learning at schools, stemming from a conventional approach that overly focuses on information transfer and offers limited scope for creativity, can be effectively addressed through the implementation of Project-Based Learning as an innovative approach. Therefore, the aim of this study is to analyze project-based learning as a means to enhance creativity skills in the English writing process of junior high school students. This study adopts a qualitative approach, where data were collected through student and teacher speeches or conversations recorded on video and noted in field journals during observations from the first to the third sessions. The qualitative data analysis follows the structured approach as per the model by Miles et al., (2018). The findings indicate that the application of Project-Based Learning in an Islamic State Junior High School in Kediri is effective in enhancing students' creativity skills in English writing, as reflected in the fulfillment of creativity indicators such as motivation, self-confidence, resilience to mistakes, initiative, humor, and critique. This research offers an innovative solution to overcome challenges in English language learning.